2015
DOI: 10.1590/0104-9224/si2002.11
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Deposition Parameters of HVOF FeMnCrSi+Ni+B Thermally Sprayed Coatings

Abstract: HVOF thermal spray process produces coatings with low porosity and low oxide content, as well as high substrate adhesion. Small variations on the parameters of the HVOF process can generate coatings with different characteristics and properties, which also is chemical composition depended of the alloy. FeMnCrSi alloy is a cavitation resistant class of material with a great potential for HVOF deposition use. The main goal of this article is to study the influence of some HVOF parameters deposition, as standoff … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Lamana, Pukasiewicz, and Sampath [24] studied the mechanism of cavitation by the detachment of WC particles sprayed by HVOF (High-Velocity Oxy-Fuel) with kerosene and propylene fuels. Sucharski et al [35] optimized the HVOF parameters standoff distance, powder feed rate, and carrier gas pressure to improve the properties of FeMnCrSiNi alloys [33], reaching the porosity 0.05%, oxide content 8.94%, tensile adhesion 40.29 MPa, and microhardness 366 HV. With the same alloys, Silveira et al [36] indicated the influence of the feedstock powder size distribution on the cavitation resistance, reaching an erosion rate of 7.8 mg/h with powders -45 µm.…”
Section: Defects and Repairing Of Runnersmentioning
confidence: 99%
“…Lamana, Pukasiewicz, and Sampath [24] studied the mechanism of cavitation by the detachment of WC particles sprayed by HVOF (High-Velocity Oxy-Fuel) with kerosene and propylene fuels. Sucharski et al [35] optimized the HVOF parameters standoff distance, powder feed rate, and carrier gas pressure to improve the properties of FeMnCrSiNi alloys [33], reaching the porosity 0.05%, oxide content 8.94%, tensile adhesion 40.29 MPa, and microhardness 366 HV. With the same alloys, Silveira et al [36] indicated the influence of the feedstock powder size distribution on the cavitation resistance, reaching an erosion rate of 7.8 mg/h with powders -45 µm.…”
Section: Defects and Repairing Of Runnersmentioning
confidence: 99%
“…Sucharski et al [31] evaluated the influence of the HVOF process parameters on the morphology of FeMnCrSi coatings, changing the standoff distance, powder feed rate, and carrier gas pressure. The porosity increased with the standoff distance and decreased with the powder feed rate.…”
Section: High-velocity Oxy-fuel Sprayed Femncrsi Coatingsmentioning
confidence: 99%
“…The quality and durability of coatings can be improved by parameter optimization of the spraying process, preparation of substrate surface for better adhesion, and automation of the process 27 . In addition, the melting conditions and structure of coatings by electric arc spraying depending on the pressure of spraying airflow, spraying angle, speed, work distance, and others, which can result in controlling the amount of the oxide phase and porosity in coatings, and mechanical characteristics like hardness, residual tensile stresses, cohesion and adhesion 13,15 .…”
Section: Coating Characterizationmentioning
confidence: 99%
“…The arc spraying process has a high deposition rate and a lower operating cost than other similar processes and the possibility of application and maintenance in-field operation. The main mechanism of adhesion and cohesion of coating is the mechanical anchoring of the splats [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%